QUORUM SENSING SCREENING OF SOME MEDICINAL PLANTS FROM MONGOLIA (Mongolian Journal of Agricultural Sciences, 2015)
The purpose of this study was to search for a novel quorum sensinginhibitor and analyseits inhibitory activity of medicinal plants of Mongolia. This study investigated the effects of some plant extracts on the bacterial communication system, expressed as quorum sensing activity. Quorum sensinghas directly propotional effect on the amount of certain compound such as pigments, produced by the bacteria. Alcohol extracts of 103 extracts of 66 medicinal plants were tested for anti-quorum sensingactivity by the Chromobacterium violaceum assay using the standard disc-diffusion method. The screening revealed the anti-quorum sensing activity of 18 extracts of 13 plants; particularly aerial part of Hedysarum alpinum L., Spongiocarpella gruboviiUlzii and Goniolimon speciosum (L.) Boiss.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 63-65